1996
DOI: 10.1034/j.1399-3054.1996.970224.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone stimulates apoplastic antioxidant systems in pumpkin leaves

Abstract: The phytotoxiticky of ozone is due to its high oxidant capacity and to its ability to generate toxic molecular species. It is well known that intracellular peroxidases play an important role in eliminating toxic forms of oxygen but little evidence has been reported on the role of peroxidases in the apoplastic compartment. The detoxification systems located in the foliar extracellular matrix and in the intracellular fluid of sensitive pumpkin plants (Cucurbita pepo L. cv. Ambassador) exposed to ozone (150 ppb. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(77 citation statements)
references
References 34 publications
(27 reference statements)
2
70
0
2
Order By: Relevance
“…If O $ was to increase cell wall rigidity this could contribute to the predisposition of O $ -exposed plants to desiccation and frost damage (Barnes et al, 1996 ;Wellburn et al, 1997) in much the same way as proposed for plants exposed to SO # \NO # (Mansfield et al, 1986). Conversely, increases in cell wall thickness would be expected to increase the tortuosity of the diffusion pathway for O $ ; increasing the residence time of the pollutant in the cell wall and thereby reducing the flux of the pollutant impinging on the plasmalemma (Heath, 1988 ;Ranieri et al, 1996 ;Lyons et al, 1999). Indeed, recent studies indicate that exposure to environmentallyrelevant concentrations of O $ can increase mesophyll cell wall thickness by c. 20% Gu$ nthardt-Goerg et al, 1997 ;Bass-Pickin & Barnes, unpublished).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…If O $ was to increase cell wall rigidity this could contribute to the predisposition of O $ -exposed plants to desiccation and frost damage (Barnes et al, 1996 ;Wellburn et al, 1997) in much the same way as proposed for plants exposed to SO # \NO # (Mansfield et al, 1986). Conversely, increases in cell wall thickness would be expected to increase the tortuosity of the diffusion pathway for O $ ; increasing the residence time of the pollutant in the cell wall and thereby reducing the flux of the pollutant impinging on the plasmalemma (Heath, 1988 ;Ranieri et al, 1996 ;Lyons et al, 1999). Indeed, recent studies indicate that exposure to environmentallyrelevant concentrations of O $ can increase mesophyll cell wall thickness by c. 20% Gu$ nthardt-Goerg et al, 1997 ;Bass-Pickin & Barnes, unpublished).…”
Section: mentioning
confidence: 99%
“…However, recent studies have revealed that many well documented antioxidants are also located in the leaf apoplast, e.g. APX (Castillo & Greppin, 1986 ;Peters et al, 1989 ;Ranieri et al, 1996), POD (Castillo et al, 1984 ;Takahama & Oniki, 1992 ;Polle et al, 1994), SOD (Castillo et al, 1987 ;Streller & Wingsle, 1994 ;Ogawa et al, 1996), ascorbate (Polle et al, 1990 ;Takahama & Oniki, 1992 ;Luwe & Heber, 1995) and small quantities of glutathione (Polle et al, 1990 ;Jamaı$ et al, 1996), although the enzymes required for the recycling of ascorbate and glutathione appear to be absent (Castillo & Greppin, 1988 ;Polle et al, 1990 ;Luwe et al, 1993). There is, therefore, the potential that O $ and\or its reactive products are scavenged before reaching the plasmalemma (Heath, 1988), and thus antioxidants located in the aqueous matrix of leaf cell walls might constitute an important first line of defence against the pollutant (Polle et al, 1995 ;Conklin et al, 1996 ;Dietz, 1997 ;Lyons et al, 1999).…”
Section: mentioning
confidence: 99%
“…The extraction buffer for superoxide dismutase (SOD) and guaiacol-POD (POD) contained 220 mM Tris-HCl (pH 7.4), 250 mM sucrose, 50 mM KCl, 1 mM MgCl 2 , 1% β mercaptoethanol and 0.01% (w/v) phenylmethylsulfonylfluoride (PMSF) [19]. For ascorbate peroxidase (APx) extraction, 50 mM Na-ascorbate was added to the buffer to prevent enzyme inactivation [19].…”
Section: Antioxidant Enzyme Assaysmentioning
confidence: 99%
“…After O $ enters the leaf through the stomata, it diffuses in the cell wall region and changes to several toxic intermediates such as superoxide anion, hydroxyl radical, hydrogen peroxide, and lipid peroxide (Castillo & Greppin, 1988 ;Badiani, 1990 ;Ranieri et al, 1996). Ascorbic acid (AA) in the extracellular space reacts rapidly with O $ and its derivatives in aqueous phase (Chameides, 1989 ;Luwe et al, 1993 ;Smirnoff, 1996).…”
Section: mentioning
confidence: 99%